Status Kesehatan Ibu dan Anak di Kawasan Tempat Pembuangan Sampah Akhir (TPA) - Dian Furwasyih; Eka Putri Prima Sari (Jurnal Kebidanan Harapan Ibu Pekalongan, 2022)
Limited health resources make people's lives around the landfill vulnerable to the risk of various diseases. The problems of housing, cleanliness, water sources, social security, education, health and survival of vulnerable groups such as children, women, and the elderly are the main problems that require special attention for the landfill area. This study aims to identify the risk of health problems for mothers and children in the TPA Air Dingin, Padang City. The research design was cross sectional with accidental sampling technique, where each respondent who met the research criteria was taken as a sample, so that a sample of 30 mothers of children under five was obtained, with 2 pregnant women, and 29 children under five. Data collection by interviewing mothers and direct examination of toddlers. Data were analyzed by computerization. It was found that 50% of pregnant women experienced 5 L, continuous nausea and vomiting, abdominal pain, high fever, severe headache and felt itching in the vulva; a small proportion of toddlers were obese, 1 toddler was stunted, a small portion do not visit the posyandu routinely, a small portion do not receive complete basic immunizations and have not received vitamin A. Education is an important point in future posyandu activities so as to help increase public understanding of the issues that occur at the moment.